Farmer Exchange Rate and Agricultural Land Conversion Analysis To Agricultural Sector Poverty in Indonesia - Indah Lestari Setiyowati; Sasongko Sasongko; Iswan Noor (Jurnal Ekonomi dan Studi Pembangunan, 2018)
The agricultural sector poverty in Indonesia is affected by some factors like income and agricultural land area. Farmer exchange rate is an indicator of farmer welfare that can be a measurement of farmer real income. Farmer exchange rate tends to be increased from 2009 to 2013. Besides, the agricultural land area tends to decrease that time. Decreasing of agricultural land is caused by agricultural land usage conversion. This research aims to analyze direct and indirect effects of farmer exchange rate and agricultural land conversion toward agricultural sector poverty in Indonesia, with the objects of 33 provinces in Indonesia (excludes North Kalimantan) from 2009 until 2013. This research is using path analysis to obtain the result, with agricultural laborer variable and agricultural productivity as intervening variables. The result obtained that farmer exchange rate has a direct and indirect effect toward agricultural sector poverty, besides agricultural land conversion has an indirect effect toward agricultural sector poverty.Keywords: Farmer Exchange Rate, Agricultural Land Conversion, Agricultural Productivity, Agricultural Sector PovertyJEL Classification: I32, Q01, Q24